YY1 (Yin‐Yang 1), a transcription factor regulating systemic inflammation, is involved in cognitive impairment of depression. Issue 3 (22nd December 2022) - Lu, Jing; Jin, Kangyu; Jiao, Jianping; Liu, Ripeng; Mou, Tingting; Chen, Bing; Zhang, Zhihan; Jiang, Chaonan; Zhao, Haoyang; Wang, Zheng; Zhou, Rui; Huang, Manli
Abstract : Aim: Clinical and preclinical studies suggest that alterations in the peripheral and brain immune system are associated with the pathophysiology of depression, also leading to changes in local glucose metabolism in the brain. Here, the authors identified Yin‐Yang 1 (YY1), a transcription factor closely associated with central and peripheral inflammation. Methods: Plasma levels of YY1, interleukin (IL) 6, and IL‐1β in major depressive disorder (MDD) were collected before and after treatment with vortioxetine, and correlation with clinical and cognitive scores was studied. Chronic unpredictable mild stress was treated with vortioxetine. Micropositron emission tomography (microPET) was used to analyze glucose metabolism and mRNA, and the protein level of the YY1–nuclear factor κB (NF‐κB)–IL‐1β inflammatory pathway were measured in related brain regions. Results: Plasma levels of YY1 and IL‐1β were significantly increased in MDD and decreased after treatment with vortioxetine. Meanwhile, the level of YY1 in plasma was negatively correlated with cognitive functions in patients with MDD and positively correlated with the level of IL‐1β in plasma. Compared with the control group, in chronic unpredictable mild stress rats, (microPET) analysis showed that the decrease of glucose metabolism in the hippocampus, entorhinal cortex, amygdala, striatum, and medial prefrontal cortex was reversed after treatment. mRNA and protein level of related molecular in YY1–NF‐κB–IL‐1β inflammatory pathway decreased in the hippocampus and was reversed by vortioxetine. Conclusion: The current study suggests that the YY1–NF‐κB–IL‐1β inflammatory pathway may play an essential role in both mood changes and cognitive impairment in depression, and may be associated with changes in glucose metabolism in emotion regulation and cognition. These findings provide new evidence for the inflammatory mechanisms of depression.